O ensino de música para crianças com autismo na educação básica: um estudo exploratório sobre a pesquisa na área e os processos epistemológicos dos educadores - Thiago Amaral Santos (2023)
It is currently very difficult to seek information about Inclusive Music Education in Basic Education, even greater when we delimit the schooling of children with Autism Spectrum Disorder (ASD) inserted in this context, in view of the peculiarities intrinsic to this environment, and the various theoretical/practical sources that permeate the way of acquiring the knowledge/making of this profession. It is important to point out that the problematizations about the music educator’s routine in basic education, regarding the inclusion of children with ASD, go beyond pedagogical knowledge, although its ultimate objective is teaching and learning. This knowledge is not in the curricular basis that constitutes the formation of music teachers, who when they come across the professional reality, perceive these gaps, and take individual directions in their continuing formations. These experiences are also part of educational epistemes. This dissertation is a collection of 3 academic articles seeking to describe actions and reflections of music teachers, on the way to new epistemes regarding the inclusion of autistic children in the classroom in inclusive music education in the initial grades of elementary school. In the first article, to bring the contextualization of the research of the Triad, Musical Education, TEA, and Basic Education (Initial Series of elementary school), a bibliographic survey of the last 10 years was made, taking as reference the first year after the sanction of the Berenice Piana Law (BRASIL, 2012), which guaranteed, at least legally, the inclusive schooling of children with ASD. In the second article, a Case Study was brought, in which it is possible to observe the construction of knowledge about inclusion, from the reflection on an experience, around one year, with a child with ASD, in a class of the second year of elementary school. In the 3rd article, the last one, is the description of a Focus Group, composed of 4 music teachers from the Early Years of Elementary School, in which the thematic axes emerged in the discussions were pointed out. The results of this exploratory study reveal that the dialectical processes of pedagogical knowledge and pedagogical making construction can reveal new ways of researching music, to improving and strengthening the epistemology of Inclusive Music Education in Basic Education.